Role of abnormal glycosylated IgA1 and interstitial transformation of glomerular endothelial cells in the development and progression of IgA nephropathy - Wanyu Jia; Wenjie Dou; Qin Wang; Huiqin Zeng; Peipei Shi; Jing Liu; Zhen Liu; Jin Zhang; Jian-Jiang Zhang (BMC, 2023)
Abstract Background IgA nephropathy (IgAN) is a common primary renal disease in childhood. Methods Twenty blood samples and renal tissue from patients with IgAN, 20 blood samples from healthy children and 10 normal renal tissue were collected. Serum Gd-IgA1 and renal Gd-IgA1, CD31, α-SMA and vimentin were measured. Results The serum Gd-IgA1 concentration in the IgAN group was significantly higher. Gd-IgA1 was not expressed in normal kidneys, which was positive in the IgAN group. Gd-IgA1 levels in serum and renal tissue were not related. The expression of CD31 decreased significantly in IgAN group, while the expression of α-SMA and vimentin increased significantly. There was no significant correlation between the renal concentration of Gd-IgA1 and CD31, α-SMA and vimentin. Conclusion The increased Gd-IgA1 in the serum and kidney may promote the pathogenesis of IgAN. The serum Gd-IgA1 cannot predict the extent of its deposition in the kidney. Endothelial mesenchymal transition (EndMT) may be involved in the pathogenesis of renal fibrosis in IgAN.